Gut microbes and immunotherapy for non-small cell lung cancer: a systematic review - Jin, Yali; Jie, Zhiqian; Fan, Xianming (Frontiers in Oncology, 2025)
Emerging evidence underscores gut microbiota’s role in modulating lung cancer immunotherapy outcomes, though specific impacts on immune checkpoint inhibitors (ICIs) and associated adverse events (AEs) require further clarity. This review synthesizes findings from 15 studies examining gut microbiota-ICI interactions in non-small cell lung cancer (NSCLC), alongside studies investigating antibiotics, proton pump inhibitors (PPIs), probiotics, and diet as modulating factors. Results indicate that Actinobacteria, Bacteroides, and Verrucomicrobiota correlate with positive ICI responses, while Bacillota shows variable associations; notably, Bacillota-enriched patients had fewer immunotherapy-related AEs. The administration of antibiotics and PPIs within a month before ICIs was linked to diminished efficacy, whereas probiotics correlated with enhanced outcomes. Plant-based diets are also aligned with dietary patterns supportive of ICIs. These findings suggest that analyzing gut microbiota composition could improve the ability to predict NSCLC patient responses to ICIs. Additionally, judicious use of antibiotics, PPIs, probiotics, and dietary adjustments may optimize immunotherapy outcomes and mitigate adverse effects.